Impact of preoperative chlorhexidine gluconate (CHG) application methods on preoperative CHG skin concentration. (30th April 2021) - Warren, Bobby G.; Nelson, Alicia; Warren, David K.; Baker, Meghan A.; Miller, Candace; Habrock, Tracey; Bongu, Jahnavi; Gowda, Abinav; Johnson, Jacob; Anderson, Deverick J.
Abstract: Elective surgical patients routinely bathe with chlorhexidine gluconate (CHG) at home days prior to their procedures. However, the impact of home CHG bathing on surgical site CHG concentration is unclear. We examined 3 different methods of applying CHG and hypothesized that different application methods would impact resulting CHG skin concentration.